(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to introduce international valuation standards and to identify the relationship between international valuation standards and international accounting and financial reporting standards in enhancing the quality of financial reporting (appropriate accounting information) through the use of statistical models for the purpose of measuring the property of appropriateness of accounting information through the use of statistical models for the purpose of proving the hypothesis that The research referred to it, and accordingly, the Francis and Kothari models were used to measure the appropriateness of accounting information (the quality of the information). The conclusions reached by the two researchers is that the setters of international accounting and financial reporting standards gave flexibility and alternatives to use them in various bodies in proportion to culture, laws and economic factors, and that this flexibility somewhat made the issue of consistency and consistency in the application of standards and may constitute an obstacle to the comparison process, so here comes the role of international evaluation standards To develop solutions from Through the application of basic mechanisms and multiple evaluation methods to determine consistency and consistency and reduce the risks of flexibility, and according to that vision, several recommendations were reached, the most important of which is that international evaluation standards have a role in enhancing the quality of financial reporting through the basic characteristics of accounting information, especially the appropriateness feature through the use of the entrance and the basis of the market on In accordance with international evaluation standards using fair (market) value to achieve the quality of financial reporting through the appropriateness feature using the statistical models referred to previously.